Pengaruh Bauran Pemasaran Terhadap Kepuasan Pasien Melalui Kualitas Pelayanan di Rumah Sakit Citra Arafiq - Susilawati; Wulandari, Siti; Yan, Andri; P, Yulia Anggraeni H (STIKES Ngesti Waluyo, 2024)
Patients expect an acceptable product or service and a good service delivery. Therefore, every hospital needs to implement excellent service. Patient satisfaction is determined by the role of product quality and the quality of services provided. Providing the best service to patients must be based on quality standards to meet the needs and desires of patients so that they are satisfied. This research aims to assess the impact of the marketing mix on patient satisfaction via service quality at Citra Arafiq Hospital Depok in 2022. This research method employs a concurrent triangulation strategy (mixed research) and a purposive sampling technique. This study's sample size was 93 respondents. Data analysis used descriptive analysis from SPSS software, measurement model analysis, and structural model from SEM software. The findings of this study indicate that the marketing mix affects patient satisfaction with a t value of 2,090 and a significance of 0,039. The marketing mix affects service quality with a t value of 12,88 and sig 0,000. Service quality affects patient satisfaction with a t value of 3,237 and a significance of 0,002. Service quality has a negative effect on patient satisfaction and there is an opposite influence of the marketing mix on patient satisfaction with service quality.